Methodology of a hierarchical and automated failure analysis and its advantages - Levent Ergün; Roman Müller Hainbach; Stefan Butzmann (AIMS Electronics and Electrical Engineering)
Several industries, particularly the automotive sector, are increasingly incorporating more electronics into their products. As a result, these products are becoming more complex and difficult to analyze. This complexity poses a significant challenge for manufacturers in proving the functional safety of their products. Not only do random faults present risks, but component tolerances can also lead to unexpected safety hazards. Current methods are struggling to keep pace with these challenges. We have identified key issues with existing methods and introduce a new approach that leverages computer automation and a model-based framework to enhance the process. We explain how this new method not only improves upon existing practices but also introduces additional capabilities.In this paper, we examine methods for proving the functional safety of electronic systems. We begin by identifying the challenges associated with current established methods. Next, we introduce our new approach, which relies heavily on computer assistance and offers novel techniques for conducting broader and more in-depth analyses of these systems. We then explain a new workflow that utilizes this approach. To illustrate its application, we provide a demonstrative example. Our conclusion summarizes our findings and results, and we share our thoughts on potential future developments.